Endoscopic transcanal tympanoplasty: a case series - Prajapati, Bela J.; Patel, Nikhil D.; Rai, Shreya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Microscopes have ruled ear surgeries for years. The invention of endoscope and its use in otorhinolaryngology have become an important alternative for use. Importance of endoscope lies in giving the operating surgeon a wider exposure of the EAC and access in various hidden areas without need of a post auricular incision. Aim of this study is to analyze the outcome of endoscopic transcanal tympanoplasty. Methods: This prospective study was conducted in the Department of ENT, B.J. Medical College, Ahmedabad, from July 2015 to July 2017. Thirty patients with tympanic membrane perforation (tubotympanic type) were included in study. Patients were followed up for a mean duration of 12 months and the outcome was analyzed. Results: The patients included in the study ranged in the age group of 15-55 years. Out of them 16 were males and 14 were females. All of them underwent endoscopic transcanal tympanoplasty. 2 out of 30 patients had graft failure while others had good graft uptake. Overall success rate was 93.3%. Conclusions: Transcanal endoscopic tympanoplasty is highly successful, safe and less traumatic and thus can be used for ear surgeries.